Analisis De La Percepcion De Alumnos Y Egresados Para Determinar Y Promover El Sentido De Pertenencia Y La Filantropia En Universidades - María Guadalupe Huesca Ramírez; Marivel Lumbreras Guzmán; Irma Alejandra Hernández Vicente; Gaspar Eduardo Fuentes Garza (European Scientific Journal, ESJ, 2017)
The objective of this article is to define what are the factors that prevent achieving a high sense of belonging in current students and graduates of a private university. The sense of belonging impacts on the level of participation of the activities triggered by the university as well as philanthropic strategies that seek to support those who need it most. To carry out this study, group sessions were held with graduates and current students. The latter were also given a survey to know their current perception of belonging and desire to participate in what promotes their university for which the result is that 94% of students would support philanthropic initiatives. On the other hand, the graduates comment that there is a lack of better communication to know what is happening in their alma mater and also to design linking models to strengthen current ties.